Medication Errors in Hospitals: A Study of Factors Affecting Nursing Reporting in a Selected Center Affiliated with Shahid Beheshti University of Medical Sciences - HamidReza Mirzaee; Davood Mostafaie; Fatemeh Estebsari; Peivand Bastani; Rouhallah Kalhor; SeyyedSaeed Tabatabaee (Research Center for Rational Use of Drugs (RCRUD), 2015)
Background: Medication errors are mentioned as the most common important challenges threatening healthcare system in all countries worldwide. This study is conducted to investigate the most significant factors in refusal to report medication errors among nursing staff. Methods: The cross-sectional study was conducted on all nursing staff of a selected Education& Treatment Center in 2013. Data was collected through a teacher made questionnaire. The questionnaires' face and content validity was confirmed by experts and for measuring its reliability test-retest was used. Data was analyzed by descriptive and analytic statistics. 16th  version of SPSS was also used for related statistics. Results: The most important factors in refusal to report medication errors respectively are: lack of reporting system in the hospital(3.3%), non-significance of reporting medication errors to hospital authorities and lack of appropriate feedback(3.1%), and lack of a clear definition for a medication error (3%). there was a significant relationship between the most important factors of refusal to report medication errors and work shift (p:0.002), age(p:0.003), gender(p:0.005), work experience(p<0.001) and employment type of nurses(p:0.002). Conclusion: Factors pertaining to management in hospitals as well as the fear of the consequences of reporting are two broad fields among the factors that make nurses not report their medication errors. In this regard, providing enough education to nurses, boosting the job security for nurses, management support and revising related processes and definitions are some factors that can help decreasing medication errors and increasing their report in case of occurrence.